Sanktuarium maryjne w Lewiczynie w XX i XXI wieku na tle dziejów miejscowości i parafii - Perzyna, Krzysztof (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The article presents the history of the cult centre, its revival and development in the 20th and 21st centuries. Lewiczyn is sometimes referred to as "small Częstochowa" of the Grójec land. The coronation of the image of Our Lady of Lewiczyn on 10 August 1975 gave new impetus to the expansion of the cult of the image. New forms of piety, (not practiced before) such as peregrinations of the image throughout the parishes of the Grójec land and beyond its borders, expanded the cult into the lands of southern Mazovia. Parish fairs, which were honoured by the presence of the hierarchs and clergy of the diocese, attracted more and more people. The richness of the spiritual life and the involvement of priests in the continuous deepening reverence for Our Lady of Lewiczyn is evidenced by numerous devotions, songs and prayers as well as publications concerning the sanctuary and devotional items, which are proof of the vitality of the work initiated decades before.